Comparative Evaluation of Intralesional Injection of Autologous Platelet Rich Plasma Versus Intralesional Injection of Corticosteroids in The Management of Resistant Oral Lichen Planus (Indian Journal of Contemporary Dentistry, 2023)
Background:Lichen Planus (LP) is a chronic mucocutaneous inflammatory disease that predominantly affects the oral mucosa, with a female predilection. The oral lesions are characterized by burning and pain which relentlessly affect the patient’s quality of life. The available treatment approaches for OLP documented to have a short term effect with potential adverse effects which further increases the demand of a novel therapeutic approach for the severe resistant lesions of OLP with a malignant potential. This double-blind, split-mouth randomized controlled trial aims to evaluate and compare the effectiveness of intralesional Autologous Platelet Rich Plasma and corticosteroid for the management of resistant OLP.Materials and methods: 28 clinically and histopathologically confirmed cases of resistant OLP were included with total 56 lesion sites divided into two groups of 28 each, in group 1 intralesional PRP and in group 2 intrealesional steroid was given. The injections were repeated for consecutive 4 weeks and then kept on regular followup. Parameters recorded on every visit were according to the Modified Escuider Index.Results: A statistically significant reduction in the lesion activity scores was found amongst the group treated with Platelet Rich Plasma as compared to the group treated with intralesional steroids.Conclusion: The use of intralesional PRP in resistant cases of OLP
Keywords: OLP, Platelet Rich Plasma, Intralesional Steroid